2007
DOI: 10.1007/s10725-007-9230-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diffusible indole-3-acetic acid from various parts of tulip plant during rapid elongation of the flower stalk

Abstract: In order to chemically identify the putative indole-3-acetic acid (IAA) and to confirm the native source of auxins account for rapid elongation of the floral stalk of tulip, we examined diffusible IAA from various parts of tulip plant during rapid elongation of the flower stalk. IAA was identified in the diffusates collected from the leaves, internodes, and floral organs with gas chromatography (GC)-mass spectrometry. The amount of diffusible IAA from different plant organs followed the order of that the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Endogenous levels of IAA in the 4 th internode in the treatment of morphactin applied at the 3rd node of tulips was highest among the samples after the treatment of auxin polar transport inhibitors (Fig. 3), suggesting strongly that polar transport of endogenous IAA produced in pistils (Xu et al, 2008) was almost completely inhibited by the application of morphactin compared to that of NPA and TIBA. Saniewski and Węgrzynowicz-Lesiak (1993) have reported that a continuous supply of auxin is necessary for tulip stem growth.…”
Section: Endogenous Levels Of Auxin In Tulip Stems After the Treatmenmentioning
confidence: 96%
See 2 more Smart Citations
“…Endogenous levels of IAA in the 4 th internode in the treatment of morphactin applied at the 3rd node of tulips was highest among the samples after the treatment of auxin polar transport inhibitors (Fig. 3), suggesting strongly that polar transport of endogenous IAA produced in pistils (Xu et al, 2008) was almost completely inhibited by the application of morphactin compared to that of NPA and TIBA. Saniewski and Węgrzynowicz-Lesiak (1993) have reported that a continuous supply of auxin is necessary for tulip stem growth.…”
Section: Endogenous Levels Of Auxin In Tulip Stems After the Treatmenmentioning
confidence: 96%
“…Saniewski and Węgrzynowicz-Lesiak (1993) have reported that a continuous supply of auxin is necessary for tulip stem growth. Xu et al (2008) examined diffusible IAA, from various parts of tulips, during rapid elongation of the flower stalk using GC-MS. The amount of diffusible IAA from different organs followed the order of that of the inter-nodes>flower organs>leaves at that time.…”
Section: Endogenous Levels Of Auxin In Tulip Stems After the Treatmenmentioning
confidence: 99%
See 1 more Smart Citation